Space use by the endemic common (weedy) seadragon (Phyllopteryx taeniolatus): influence of habitat and prey. Issue 1 (10th November 2021) - Allan, Sam J.; O'Connell, Max J.; Harasti, David; Klanten, O. Selma; Booth, David J.
Abstract: The weedy seadragon ( Phyllopteryx taeniolatus : Syngnathidae) is an iconic fish endemic to the southern coastal waters of Australia. The authors of this study analysed the habitat preferences and factors influencing microhabitat selection by P. taeniolatus in a population from Kurnell, NSW, Australia. Using field surveys and the resource selection probability function, the authors determined that P. taeniolatus significantly preferred kelp ( Ecklonia radiata ) – dominated habitat and avoided rock‐dominated habitat. They showed P. taeniolatus preferred habitat of between 40% and 80% coverage of Ecklonia, while avoiding areas of <20% cover. Furthermore, across all habitats, mysid prey availability significantly influenced P. taeniolatus habitat selection. The strong dependence of P. taeniolatus on Ecklonia habitat shown in this study was previously untested and highlights that reductions in Ecklonia cover under climate change, or impacts from increasing urbanisation, may render seadragon populations vulnerable to declines.